THE STRUGGLE OF BUKHARA MILITARY COMMISSION AGAINST THE NATIONAL OPPOSITION - Zokirov Bobir Chorievich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the Bukhara People’s Soviet Republic, the Bolsheviks established punitive bodies and military units in order to strengthen the Soviet power and fight against the independentists. 29 military units are stationed in the cities of Old Bukhara, New Bukhara (Kogon), Karmana, New Chorjui, Old Chorjui, Karki, Termiz.